RANCANG BANGUN SISTEM KEAMANAN RUMAH DENGAN DUA TINGKAT PENGAMANAN MENGGUNAKAN RFID DAN PASSWORD - Fatfa, Asgar Irmawan Andi; Rasmana, Susijanto Tri; Harianto, Harianto (Journal of Control and Network Systems (JCONES), 2017)
As a result of the current economic crisis that is currently sweeping Indonesia, many Indonesian people lose their jobs, so the unemployment rate is quite high, and the average of crime is too much. Especially the act of theft or robbery of the increasing and often occurs in residential complex arguing that economic pressure due to the lack of work that can be relied upon to meet daily needs.In this research built home security which have two levels of security using RFID and Password. RFID is an identification system without a cable that allows the retrieval of data without having to touch such as barcode and magnetic card, which is installed at the gate that is useful to create a security system, and a keypad for Password mounted in each door indoor rooms are useful for providing security in case one code then the buzzer will sound, and use the Arduino Mega 2560 as mikrokontrolernya. Based on the results of the testing tool indicate the level of success in determining the success rate correctly by 86%, and the error rate tool in determining the error rate of 14%..Keyword : RFID, Password, Buzzer, Arduino mega 2560.